Implementasi Program Gerakan Literasi Sekolah Pada Tahap Pembiasaan Membaca - Fidafatul Hidayati; Ma’as Shobirin; Fitria Martanti (MAGISTRA: Media Pengembangan Ilmu Pendidikan Dasar dan Keislaman, 2020)
Abstract This research study about implementation of literation movement program of reading habbit steps for 4th grader in SDN Sampangan, study about impact and teacher’s role in conducting literation program. This research is field research with use qualitative approach. Technique of data collection is conducted by documentation, observation and interview. Technique of data analysis is done by data reduction, data presentation, and making conclusion while to check data validity is done by observation, triangulation technique and triangulation sources. The result show that The Implementation of Literation Movement Program on Reading Habituation Step for 4th Grader in SDN Sampangan 02 through six steps. First, giving time 10-15 minutes for reading. It can be conducted in class or out of class. Summerize what they are read from the textbook. Retelling what they are read in front of the class. Giving appreciate for student who are already retelling in front of the class and making a note for book which are already read and borrowed by the student in reading card. Positive impact of this activity is there are daily reading habbit which make students become keen on reading and improving their reading references. The role of 4th grader teacher are as assistant and facilitator.